PEWARISAN TRADISI LISAN PERTUNJUKAN SENI DENDANG MASYARAKAT SERAWAI BENGKULU - Lubis, Bustanuddin; Yoesoef, Muhammad; Pudentia (Jurnal Korpus, 2023)
The focus of this research is to reveal the inheritance of the tradition of performing seni dendang Serawai in Bengkulu. The performance of the seni dendang Serawai is a traditional performance that is shown during the bimbang adat ceremony (traditional wedding ceremony) performed by the cultural studio in the Serawai ethnic community. The research method used is qualitative research using direct observation data collection techniques and direct interviews with the head of the cultural center. The data collected is processed based on the concept of transmission. The results of the research found that the unsi Harapan Bersama in Seluma Regency was still trying to maintain and pass on the seni dendang of the Serawai people. The inheritance of the performing seni dendang is carried out openly through a process. The inheritance process that is carried out is carried out by the dendang players in an active and passive way. The performances of seni dendang are passed down from generation to generation.